Synthesis, Characterization and Biological Study of the Ligand 2-methyl-5-[(2E)-2-(4-Nitrobenzylidene) Hydrazinyl]- 1, 3, 4-Oxadiazole with some of its Transition Metal Complexes - Zainab M. Kareem (Journal of Global Pharma Technology, 2020)
A new series of transition metal ions (Cr (III), Co (III), Cu (II) and Ni (II) complexes with the ligand 2-methyl-5-[(2E)-2-(4-nitrobenzylidene) hydrazinyl]-1, 3, 4-oxadiazole were synthesized. A ligand was synthesized by reaction hydrazine hydrate with ethyl acetate in ethanol as solvent , the product reaction with potassium hydroxide and carbon disulphide to give 5-methyl-1,3,4-oxadiazole-2-thaiol, the product was reacted with hydrazine hydrate again to produce 2-hydrazinyl-5-methyl-1,3,4-oxadiazol. The resultant was mixed with parnitro-benzldehyde to produce the ligand (L2). The newly synthesized compounds were characterized by Fourier transform infrared (FTIR) Spectroscopy, Nuclear Magnetic Resonance Spectroscopy (1H NMR), elemental analyses (C, H, N), Mass Spectra data. The program Hyperchem 7.51 have been used for theoretical calculation using PM3 method to study the electrostatic potential, electron density, heat of complexation. It has been shown through all the above diagnostic measures that ligand is formed with the (Cu, Co and Ni) ions tetrahedral complexes and with the Cr formed octahedral complex. The biological study of ligand and its complexes showed that all prepared compounds have antibacterial against three types of bacteria and there was high percentage of hemolysis. Keyword: 1, 3, 4-Oxadiazole derivative, Antibacterial, Hyperchem, Hemolysis.